Buku teks amalan bahasa Melayu tingkatan peralihan - Nazir, Faridah (Dewan Bahasa dan Pustaka., 2019)
Amalan Bahasa Melayu's textbook for Transition Form has four thematic areas of knowledge of history, science, mathematics, and Design and Technology. The scope of the theme for each field of knowledge is selected in accordance with the abilities and capabilities of the transition class students who face the problem of vocabulary proficiency and adjusted understanding of the language according to the context of the subject. Teachers Practice Malay should determine the theme, the standard of teaching and learning activities in accordance with the details of the theme, in addition to strategies, methods, and techniques to ensure that students master the goals and objectives of the course. Each lesson is taught standard should emphasize proficiency approach that focuses on listening and speaking, reading or writing to ensure an increased level of student mastery of the Malay language classes.